Applied social research a tool for the human services - Monette, Duane R.; DeJong, Cornell R.; Sullivan.T.J; Hilton.T.P (Brooks/Cole Cengage Learning, 2014)
Presenting social science research methods within the context of human service practice is the ideal text for you as you pursue your studies in human services, counseling, social work, sociology, criminal justice, or community planning.